Culturally responsive multimedia tool framework for dyslexic children in Malaysia: a preliminary study - Balamuralithara Balakrishnan,; Hor, Beng Chong; Muhamad Zaffwan Idris,; Ahmad Nizam Othman,; Muhammad Fadhil Wong,; Mohamed Nor Azhari Azman, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Cultural and language factors may aggravate difficulties associated with dyslexia and thus need to be studied. Malaysia is a multiracial and multicultural country comprising Malay, Chinese, Indian, Kadazan, Iban and other ethnic groups. There are many multimedia teaching and learning course-wares for dyslexic children to learn English but none of the courseware takes into account the cross-cultural difficulties ad impediments, in particular, the phonological difficulties faced by individuals with dyslexia. This study examined a framework that could integrate cultural and linguistic factors for Malaysian dyslexic English language learners. This tool would substantially benefit the instructors who train the dyslexia students as well.